DIVISION OF INHERITANCE OF INDONESIAN CITIZEN CHILDREN ADOPTED BY FOREIGNERS ACCORDING TO INDONESIAN CIVIL INHERITANCE LAW PEMBAGIAN WARISAN ANAK WARGA NEGARA INDONESIA YANG DIADOPSI WARGA NEGARA ASING MENURUT HUKUM WARIS PERDATA INDONESIA - Davina Dewi; Handar Subhandi Bakhtiar (Jurnal Hukum DE'RECHTSSTAAT, 2023)
ABSTRACT Not all married couples are immediately given children from their relationship. Therefore, many couples choose to adopt children, because they do not get offspring. Child adoption in Indonesia consists of two types, namely, child adoption between Indonesian citizens and child adoption between Indonesian citizens and foreigners. The requirements and procedures for the adoption of Indonesian children by foreigners are regulated in Government Regulation No. 54/2007 on the Implementation of Child Adoption and Minister of Social Affairs Regulation No. 110/2009 on Child Adoption Requirements. Like biological children, adopted children also have the opportunity to inherit from their adoptive parents. The Civil Code recognizes the term testament or will. The purpose of this writing is to understand the requirements that must be met by foreigners when they want to adopt Indonesian children and analyze how the distribution related to the inheritance rights of Indonesian children who have been adopted by foreigners based on Civil Inheritance law. The type of research used in this research is normative juridical with a Statute Approach and Conceptual Approach. The result of this research is that foreigners can adopt Indonesian children as a last resort but must fulfill the conditions regulated by Indonesian law. Foreign adoptive parents can provide testamentary grants addressed to their adopted children. So that one day the adopted child can receive inheritance when the adoptive parent has passed away. However, this testamentary grant must not reduce the absolute rights or Legitime Portie of the biological child. Keywords: Adoption, Child, Foreigner, Inheritance, Civil Law. ABSTRAK Pengadopsian anak di Indonesia terbagi menjadi dua jenis yaitu, pengadopsian anak antar WNI dan pengadopsian anak antara WNI dengan WNA. Syarat-syarat dan cara pengadopsian anak WNI oleh WNA telah diatur dalam PP Republik Indonesia No. 54 Tahun 2007 Tentang Pelaksanaan Pengangkatan Anak dan Permensos No. 110 Tahun 2009 tentang Persyaratan Pengangkatan Anak. Dalam KUHPerdata mengenal istilah testament atau surat wasiat. Jenis penelitian menggunakan yuridis normatif dengan pendekatan Perundang-undangan dan Konseptual. Hasil dari penelitian ini adalah WNA bisa mengadopsi anak WNI sebagai upaya terakhir tetapi harus melengkapi syarat-syarat yang telah diatur pada peraturan Indonesia . Orang tua angkat WNA dapat memberikan hibah wasiat yang ditujukan untuk anak angkatnya. Agar kelak anak angkatnya dapat menerima warisan ketika orang tua angkatnya telah meninggal dunia. Namun hibah wasiat ini tidak boleh mengurangi hak mutlak atau Legitime Portie sang anak kandung dan ahli waris keturunan garis lurus sang pewaris. Kata Kunci: Adopsi, Anak, WNA, Waris, Hukum Perdata.